2015
DOI: 10.1097/rlu.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Neck Pinhole Dual-Tracer and Dual-Phase MIBI Accuracies With and Without SPECT/CT for Parathyroid Adenoma Detection and Localization

Abstract: In this large patient group, the accuracy and certainty of PA diagnosis/localization were higher in pinhole DT SPECT/CT than all other parathyroid scintigraphy protocols. Pinhole DT better identified PA than pinhole DP, whereas SPECT/CT improved PA localization in both protocols. Pinhole DP showed limited contribution and thus should be only considered when PA diagnosis/localization is uncertain by pinhole DT SPECT/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Heiba et al 22 compared neck pinhole dual-tracer and dualphase sestamibi with and without SPECT for localization of 153 parathyroid adenomas, and they found that pinhole dual-tracer SPECT had significantly higher sensitivity (93%) than dual-phase SPECT (68%), SPECT with only pinhole delay (39%), pinhole dual-tracer CT alone (25%), and dual-phase CT alone (18%). In a prospective study comparing dual-isotope subtraction pinhole scintigraphy, dual-phase SPECT, 4DCT, and sonography in 91 patients with 97 parathyroid adenomas, Krakauer et al 23 found that the sensitivity of dual-isotope subtraction pinhole scintigraphy was 93%.…”
Section: Discussionmentioning
confidence: 99%
“…Heiba et al 22 compared neck pinhole dual-tracer and dualphase sestamibi with and without SPECT for localization of 153 parathyroid adenomas, and they found that pinhole dual-tracer SPECT had significantly higher sensitivity (93%) than dual-phase SPECT (68%), SPECT with only pinhole delay (39%), pinhole dual-tracer CT alone (25%), and dual-phase CT alone (18%). In a prospective study comparing dual-isotope subtraction pinhole scintigraphy, dual-phase SPECT, 4DCT, and sonography in 91 patients with 97 parathyroid adenomas, Krakauer et al 23 found that the sensitivity of dual-isotope subtraction pinhole scintigraphy was 93%.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23]26 Multiple studies in the literature compare the performance of parathyroid scan to other anatomic imaging modalities. 10,24,25 Also in most institution, parathyroid scintigraphy is complemented with other anatomic imaging modalities; ultrasound, CT, and/or MRI for the localization of parathyroid adenomas. Our study aims to optimize the utility and interpretation of Tc-99m SPS with SPECT/CT for the diagnosis and localization of the abnormal parathyroid gland.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually a combination of ultrasound and parathyroid scan. 24,25 Additional imaging modalities as MRI or 4D CT may be thought for discordant or inconclusive results between US and parathyroid scans. 10 Our study evaluated the accuracy and outcomes from a standardized simple method of interpretation and reporting of Tc-99m sestamibi dual-phase scan with SPECT/CT as the imaging modality for the diagnosis and localization of parathyroid adenoma in patients with PHPT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a meta‐analysis showed a range of sensitivities for sestamibi SPECT/CT from 28% to 98%, likely attributable to varying techniques, levels of expertise, and/or varying patient population. In addition, variable results even within single high‐volume centers have been reported, such as significantly different sensitivities on sestamibi scans for overlapping groups of patients from a similar time period (93% vs 74%) …”
Section: Practice Setting Realitymentioning
confidence: 99%